On the continuity of harmonically conjugated functions in the Jordan domains - Pritsker, I. E. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We study sufficient conditions for the continuity of harmonically conjugate functions in dependence of the geometrical structure of various classes of Jordan domains. The results obtained are generalizations of the well–known Dini continuity condition for functions on the disk.